2005
DOI: 10.1007/s00213-004-2137-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional BDNF polymorphism and anxiety-related personality traits

Abstract: Our findings support the hypothesis that anxiety- and depression-related personality traits are associated with the BDNF polymorphism although the explained variance is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
155
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(180 citation statements)
references
References 44 publications
20
155
1
4
Order By: Relevance
“…20 In studies with respect to personality traits, the C allele was associated with anxiety-related personality traits, such as higher mean neuroticism scores in the NEO-FFI, 21 and higher levels of trait anxiety in the STAI. 22 Interestingly, the frequency of the T allele in the Japanese and other Asian populations (approximately 41%) was significantly higher than that (approximately 18%) in Caucasians. 23 Thus far, two genetic association studies investigated this variant of the BDNF gene in PD, which observed no significant association in the Japanese or Chinese population.…”
Section: Introductionmentioning
confidence: 87%
“…20 In studies with respect to personality traits, the C allele was associated with anxiety-related personality traits, such as higher mean neuroticism scores in the NEO-FFI, 21 and higher levels of trait anxiety in the STAI. 22 Interestingly, the frequency of the T allele in the Japanese and other Asian populations (approximately 41%) was significantly higher than that (approximately 18%) in Caucasians. 23 Thus far, two genetic association studies investigated this variant of the BDNF gene in PD, which observed no significant association in the Japanese or Chinese population.…”
Section: Introductionmentioning
confidence: 87%
“…In a recent study, Kaufman et al found that children carrying the met allele of the BDNF gene val66met polymorphism and two short alleles (s/s) of 5-HTTLPR had the highest depression scores, but that this vulnerability was only evident in children with maltreatment history (Kaufman et al, 2006). This result is somewhat surprising, because most reports studying the val66met polymorphism have suggested that the met allele is protective for anxiety (Lang et al, 2005;Hunnerkopf et al, 2007) depression (Schumacher et al, 2005;Strauss et al, 2005;Frodl et al, 2007), but see Jiang et al (2005), and bipolar disorder (Neves-Pereira et al, 2002;Sklar et al, 2002). Indeed, in a separate study, the prevalence of depression due to multiple life events was found to be dramatically increased in s/s elders with one met allele (Kim et al, 2007).…”
Section: Genetic Epistasismentioning
confidence: 99%
“…[24][25][26][27][28][29] Further evidence implicating the BDNF locus' involvement in mood disorders arises from studies of neuroticism, a trait highly correlated with depression. [30][31][32][33] We have recently described an association between the BDNF (GT) n marker and a haplotype containing the Val 66 Met val allele with COMD in 93 case-control pairs. 34 Overall, substantial reason exists to further examine BDNF as a candidate gene for depressive disorders such as COMD.…”
mentioning
confidence: 99%